Cooperative Collection Development: Significant Trends and Issues, 1st edition - Simpson, Donald B. (Routledge, 2020)
This book, first published in 1998, examines formal cooperative collection development programs as well as nonformal agreements. It analyses the most effective mechanisms for establishing a cooperative collection agenda, including making the most economical use of library funds; inadequate delivery mechanisms; and the effects of the Internet on the expectations of library patrons and how interlibrary loans can help. It concludes that a library's collection development future may lie in providing financial subsidies to fund large storehouses of digital records.